The physiotherapeutic procedures in patients with or without osteoporotic fractures - Grześkowiak, Marcin; Leszczyński, Piotr; Lewandowski, Jacek (Menopause Review/Przegląd Menopauzalny, 2013)
Osteoporotic fractures are one of the worst complications of osteoporosis. Decreasing the main risk factors for falls and improving the quality of life and physical fitness among patients with osteoporotic fractures are the main objectives of physiotherapy treatment. The aim of this paper is to present the characteristics of physiotherapeutic procedures and to lay down guidelines for medical doctors who are treating such patients. The contents of this article are based on the authors’ own experience and observations and also on the latest reports from the literature on the subject. The main element of treating patients with or without osteoporotic fractures is therapeutic exercises supported by physical medicine. At the same time, proper education of those patients is also very important. In conclusion, therapeutic exercises, physical medicine and patients’ education are the main elements of therapy for patients with or without osteoporotic fractures.